Transformation of the SITR Mathematical Model into Batik Motifs: Visualization of Tuberculosis Transmission in Makassar City through MATLAB Simulation - Faisal, Achmad; Syifariyadi, Nada Aliyah; Asura, Nahli Pramesta; Sugiyanto, Sugiyanto (Proceeding International Conference on Religion, Science and Education, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are the main drivers of Indonesia’s economy, particularly in Cirebon City, which is rich in cultural heritage and local wisdom. However, many MSMEs face obstacles in scaling up due to limited digital adoption, traditional management practices, and restricted market access. This study aims to examine digital transformation in the strategic management of MSMEs through the development of a sales application that integrates elements of local wisdom to strengthen competitiveness and support MSMEs in Cirebon to move up to a higher business level. This research applies a mixed-method approach, combining interviews with MSME actors and stakeholders as qualitative data with digital adoption readiness analysis as quantitative data. The application development follows the System Development Life Cycle (SDLC) framework with a user-centered design to ensure relevance to business needs. Key features include sales reports, supplier data, product data, and sales graphs. The findings show that the application improves operational efficiency and supports data-driven decision-making. Moreover, the integration of cultural identity within the digital platform contributes to the preservation of local wisdom while fostering sustainable business growth. This study highlights that digital transformation, when combined with culture-based strategic management, can serve as a pathway for MSMEs to upgrade their business class while aligning with national economic priorities and global sustainable development goals.